The Simulation of Commercial Vehicle Border Crossing of Thailand – Malaysia : Case study of Sadao Border, Songkhla - Suttishe, Palida; Sirivongpaisal, Nikorn; Kongkaew, Wanatchapong (RMUTP Research Journal Sciences and Technology, 2019)
Border crossing trade can an important role in the competitiveness of Thai products in neighboring countries as Thailand has a geographical advantage that connects with neighboring countries, making border trade an important part of generating revenue for the country. The Thailand - Malaysia border trade study showed that the transit process took a long time, resulting in a waiting truck at the checkpoint, causing traffic jams and the congestion and congestion of the customs. As a result, the average waiting time of the system takes up to 264.19 minutes per trip and transportation cost from 7,141.87 baht per trip by reducing the waiting time from the process to 13.41 minutes per trip, it was found that the transportation cost was 6,975.16 baht per trip (Decrease of 166.71 baht). Reduction the transportation costs and waiting times enhance the potentiality and the competitiveness of border crossing